Educating global citizens in business schools. (2014) - ,; ,; ,
Abstract : Purpose – Global citizenship, social responsibility and sustainability are constructs increasingly used in business schools. Yet, there is no widely accepted definition or conceptualization of the global citizen, nor is there strong evidence of how the global citizen is effectively translated into university ethos, culture and practice. This paper aims to conceptualize the global citizen in higher education broadly and more specifically in regard to business schools.Design/methodology/approach – International higher education, social science and business literature has been reviewed to present an integrated understanding of the global citizen; contextualized to higher education generally and business schools specifically.Findings – It is argued that the global citizen, viewed through a moral and transformative cosmopolitan lens, provides an alternative to the rhetoric frequently paid to the construct. This paper describes "global citizen learning" underpinned by the social imaginary, relationality and reflexivity. These virtues equip the students' global business mindset for complexity and ambiguity.Research limitations/implications – The interdisciplinary literature reviewed in this paper brings a focus to moral reasoning, sensitivity and values‐based teaching. These aspects create new ways for the global citizen to be more explicitly integrated into business ethos and curricula.Practical implications – Global citizen learning provides the "conceptual glue", needed to link social responsibility, sustainability and ethical principles to business curricula. Also, the paper outlines how "global citizen learning" can be utilized in existing curricula from a practical perspective.Originality/value – This paper discusses values and moral reasoning in business education. It is proposed that the global citizen conceptualized through moral and transformative cosmopolitanism provides a humanistic buffer to the neoliberal growth paradigm.